THE ROAD CHRONOTOPE IN MODERN UKRAINIAN LITERARY FAIRYTALES - Дибовська, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the chronotope of road in fairytales. The researches by Ukrainian and foreign scientists are analyzed. The models of chronotope of the road according to the specific features of literary fairytales are defined. The presence of the chronotope of the road in modern Ukrainian literary fairytales is analyzed too.